COMPARISON ANALYSIS OF FINANCIAL PERFORMANCE BETWEEN PT. BANK CIMB NIAGA, TBK AND BANK MANDIRI (PERSERO) TBK - Palit, Friscelia Christine (Universitas Sam Ratulangi, 2013)
Bank is a company that provides financial services for the whole society. It is important for bank to go public which is the process of transformation from private company into a public company. The owner of a bank wants the management to optimize the existing resources as much as possible. Ownership of banks in Indonesia spread, partly owned by the government, partly owned by private domestic and foreign private. Research objectives are to analyze financial performance between foreign and local banks that go public in Indonesia. Analytical techniques used to see comparison of financial performance between foreign and local banks is the method of Independent sample t-test. The implementation of this method is to compare the financial performance each year from 2009 until 2012 and simultaneously. The data used in this research is gathered from IDX. The conclusion is there are significant differences for ratio of NPL, ROE, and LDR. While the ratio of CAR and ROA there was not a significant difference. In terms of profitability, capital financial performance of Bank Mandiri is better than Bank CIMB Niaga. But, there is a lower ratio of Bank CIMB Niaga, which is liquidity ratio (LDR). To improve this ratio, Liquidity ratio (LDR) can be enhanced by pressing the increase of funds channeled through bank financing or loans to customers. While Bank CIMB Niaga performance was better in terms of liquidity, but there are some lower ratios of this bank which are NPL and ROE. To improve NPL ratio bank CIMB Niaga must careful in lending to customers to reduce the amount of non-performing loans.Â And the bank should increase the profitability ratios (ROE) as well as increasing dividend payments, in order to give high confidence to investors, about bank prospects in the future. It means that bank should be more efficient in their operations in order to increase bank profits so as to increase the stock return. Keywords: financial performance, financial ratio